Experimental simulation of liquid entrainment in ADS-4 depressurization line in AP1000. (August 2016) - Xiang, Y.; Wu, Y.W.; Sun, D.C.; Tian, W.X.; Zhang, P.; Qiu, S.Z.; Su, G.H.
Abstract: The fourth stage Automatic Depressurization System is an important passive safety feature in Westinghouse AP1000 which enables controlled depressurization of reactor coolant system in small break LOCA. However, large amount of coolant can be carried to the containment via the ADS-4 branch entrainment and the upper plenum entrainment during the depressurization process, which poses great threats to core uncovering and melting. The automatic Depressurization and Entrainment TEst Loop (ADETEL) modeled after AP1000 with a scaling ratio of 1:5.6 was constructed to investigate the entrainment and depressurization behavior after the actuation of ADS-4 valves. The entrainment and depressurization features were investigated under different initial pressure, mixture liquid level in the pressure vessel and heating power. The entrainment deposition effect of the reactor internals was also investigated. The test data reveals that large amount of water are entrained through the ADS-4 branch line within a short period of time. The liquid entrainment rate and the reduced rate of the mixture liquid level in the pressure vessel increase with the initial system pressure. It is notable that the core uncovery was experienced when the initial pressure was set to 0.5 MPa in current experimental conditions. The reactor internals have little effect on the entrained mass and the mixture liquid levels in the pressure vessel. Highlights: ADETEL facility scaled after AP1000 with a ratio of 1:5.6 was constructed. Simulation tests were conducted with steam-water. The entrainment and depressurization feature of ADS-4 was investigated. The entrainment deposition effect of reactor internals were investigated.